Petrography of Sandstones from the Kamlial and Chinji Formations, Southwestern Kohat Plateau, NW Pakistan: Implications for Source Lithology and Paleoclimate - Ullah, Kafayat; Arif, Mohammad; Shah, Mohammad Tahir (Journal of Himalayan Earth Sciences, 2006)
The Kamlial and Chinji formations of the southwestern Kohat plateau (Himalayan Foreland basin) dominantly consist of sandstones and shales deposited in a terrestrial foreland basin that developed in response to the Himalayan orogenic movements. Detailed petrographic studies of representative samples from three different sections reveal that both the Kamlial and Chinji sandstones contain abundant quartz with subordinate feldspars, variable proportions of lithic grains, accessory amounts of micas and traces of a number of heavy minerals. The feldspar content mostly ranges from 18 to 30% and 24 to 28% in the Kamlial and Chinji sandstones, respectively. The abundance of lithic grains shows a wide range of variation (11 to 35%). Although the lithics are mainly sedimentary, but fragments of volcanic and low-grade metamorphic rocks also occur in appreciable amounts. Micas, including both muscovite and biotite, are generally less than 10 % of the total detrital grains. The observed heavy minerals include epidote, monazite, apatite, garnet, zircon, rutile and brown hornblende. The crystals of zircon, monazite, rutile, epidote and mica also occur as tiny inclusions in quartz grains. On the basis of modal composition, the Kamlial and Chinji sandstones fall into the groups of feldspathic and lithic arenites. The former mostly originates by the weathering of feldspar-rich crystalline rocks whereas the latter is believed to be derived from rugged high-relief source areas. The presence of appreciable amount of feldspars in all the studied sandstone samples favors either high relief or arctic climate at the source area. The overall variation in the relative abundance of different types of quartz grains (monocrystalline including both non-undulatory and undulatory types and polycrystalline containing 2-3 and >3 subgrains) in the Kamlial sandstone indicates derivation from medium-high grade metamorphic rocks with subsidiary contribution from low grade metamorphic rocks. In comparison, the same parameter shows almost equal contribution from medium-high grade and low-grade metamorphic rock provenance for the Chinji sandstone. Similarly, the consistent presence of mica, epidote, and garnet also indicates a source region composed of metamorphic rocks. On the other hand, the average contents of different types of quartz grains from the Kamlial and Chinji Formations show granitic and/or gneissic source. The greater abundance of alkali feldspar than plagioclase further supports this conclusion. Similarly, the higher amount of non-undulatory monocrystalline quartz than the undulatory one suggests the presence of plutonic and volcanic rocks in the source area or, alternatively, a long distance/amount of transport of the detritus. Furthermore, the intersectional variation in modal composition and types of quartz grains in both the Kamlial and Chinji sandstones suggest a strong spatial control on their deposition.